2007
DOI: 10.1016/j.imbio.2006.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The SARS coronavirus spike glycoprotein is selectively recognized by lung surfactant protein D and activates macrophages

Abstract: The severe acute respiratory syndrome coronavirus (SARS-CoV) infects host cells with its surface glycosylated spike-protein (S-protein). Here we expressed the SARS-CoV S-protein to investigate its interactions with innate immune mechanisms in the lung. The purified S-protein was detected as a 210 kDa glycosylated protein. It was not secreted in the presence of tunicamycin and was detected as a 130 kDa protein in the cell lysate. The purified S-protein bound to Vero but not 293T cells and was itself recognized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
114
2
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 47 publications
3
114
2
2
Order By: Relevance
“…The slight decrease in SP-D could enhance the SARS infection, although this is unlikely, based on our experiments with 229E-6V (another coronavirus), in which SP-D did not make a major difference in the 229E-6V infectability of human alveolar macrophages (45). Nevertheless, SP-D has been reported to interact with the SARS spike glycoprotein, the attachment protein (46).…”
Section: Discussionmentioning
confidence: 82%
“…The slight decrease in SP-D could enhance the SARS infection, although this is unlikely, based on our experiments with 229E-6V (another coronavirus), in which SP-D did not make a major difference in the 229E-6V infectability of human alveolar macrophages (45). Nevertheless, SP-D has been reported to interact with the SARS spike glycoprotein, the attachment protein (46).…”
Section: Discussionmentioning
confidence: 82%
“…Thus, SP-A, SP-B, and SP-D are generated by alveolar type II and airway epithelial cells, while SP-C is exclusively synthesized by type II cells. Also known as collectins, SP-A and SP-D facilitate the elimination of invading pathogens by enhancing phagocytic activity of macrophages (23,38,39). SP-A-deficient mice exhibit an exaggerated inflammatory response to influenza virus infection (40).…”
Section: Discussionmentioning
confidence: 99%
“…The alveolar lining is covered by alveolar type I and type II epithelial cells, which play essential roles in fluid balance and in secretion of surfactant proteins SP-A, SP-B, SP-C, and SP-D (21)(22)(23)(24). Although enhanced lethality in macrophage-depleted animals is attributed to elevated virus titers, the fate of alveolar epithelial cells in macrophage-depleted animals after influenza virus infection is unclear.…”
mentioning
confidence: 99%
“…Two important proteins of the innate immune system in the gas exchange portion of the lung are surfactant proteins A and D (Haagsman et al, 2008;Pastva et al, 2007), both of which have been reported to be important in controlling viral infections (Doss et al, 2009;Leth-Larsen et al, 2007). BALF samples from SDAV and control rats were assayed for surfactant proteins SP-A and SP-D using ELISA (Fig.…”
Section: Rat Lung Infection By Sdav Induces Expression Of Cytokines Lmentioning
confidence: 99%